Evaluation of hot and cold extraction of bioactive compounds in teas. (20th June 2015) - de Carvalho Rodrigues, Vanessa; da Silva, Marcos V.; dos Santos, Adriele R.; Zielinski, Acácio A. F.; Haminiuk, Charles W. I.
Summary This study evaluated the bioactive compounds of different types of tea by comparing hot and cold infusions. A multivariate data analysis was carried out, where the principal components analysis (PCA) and hierarchical cluster analysis (HCA) were used. Phenolic compounds varied between 267.27–2896.00 mg GAE L−1 and 215.10–7351.33 mg GAE L−1 for hot (80 °C) and cold extraction (20–25 °C), respectively. In the case of their antioxidant activity, results with DPPH were 43.10‐73.67% for hot extraction and 46.80‐77.13% for cold extraction. The average values for the ABTS˙+ method ranged between 2535.43 and 33 300.17 μmol TE L−1 and between 1110.34 and 38 300.67 μmol TE L−1, respectively, for hot and cold extraction. Different compounds were identified by liquid chromatography in the samples evaluated, where caffeine presented the higher concentrations in the teas. Samples of green and black tea (hot extraction) and white tea (cold extraction) showed bacteriostatic activity for S. aureus and E. coli. No extract had any bactericide activity. The current study revealed that cold infusion was more efficient in the extraction of bioactive compounds.